Lessons from Walden : Thoreau and the crisis of American democracy - Taylor, Bob Pepperman (University of Notre Dame Press, 2020)
"Throughout this original and passionate book, Bob Pepperman Taylor presents a wide-ranging inquiry into the nature and implications of Henry David Thoreau's thought in Walden and Civil Disobedience. As Taylor says in his introduction, "Walden is a central American text for addressing two of the central crises of our time: the increasingly alarming threats we now face to democratic norms, practices, and political institutions, and the perhaps even more alarming environmental dangers confronting us." Taylor pursues this inquiry in three chapters, each focusing on a single theme: chapter 1 examines simplicity and the ethics of "voluntary poverty," chapter 2 looks at civil disobedience and the role of "conscience" in democratic politics, and chapter 3 concentrates on what "nature" means to us today and whether we can truly "learn from nature"--And if so, what does it teach? Taylor considers Thoreau's philosophy, and the philosophical problems he raises, from the perspective of a wide range of thinkers and commentators drawn from history, philosophy, the social sciences, and popular media, breathing new life into Walden and asking how it is alive for us today. In Lessons from Walden, Taylor lets all sides have their say, even as he persistently steers the discussion back to a nuanced reading of Thoreau's actual position. With its tone of friendly urgency, this interdisciplinary tour de force will interest students and scholars of American literature, environmental ethics, and political theory. It deserves to be read by a more general readership, including environmental activists, concerned citizens, and anyone troubled with the future of democracy"--